The gender identity of Algerian women during French colonialism A semiological study of the art portrait of an Algerian girl in the karakou by the American painter Frederick Arthur Bridgman in 1888AD - نور الإسلام غدار (International Journal of Social Communication, 2022)
Through this study, we seek to give profiles of the gender identity of Algerian women in the most important historical stations of Algeria through various artistic works. And that's through a semiotic study of the art portrait by the American artist Arthur Bridgman in 1888 AD, in which he portrayed part of the reality of Algerian women in the colonial period. Where we reached a number of results, the most important of which is that the artistic image carries many gender connotations for Algerian women in that period, where the physical anatomy of the girl was characterized by beauty, elegance, patience, talent and challenge. The structural formations indicated their functions and position in society.